Women Representation in Barbie 2023: A Critical Discourse Analysis - Siti Hanifatur Rohmah; Rohmani Nur Indah (STAIN Sultan Abdurrahman Kepulauan Riau, 2026)
One manifestation of gender injustice is the unequal representation of women in the entertainment and media industries particularly in movies. In Barbie 2023, the characters play a substantial role in depicting the reality of gender issues. This research aims to analyze how women are represented in the 2023 Barbie film. It employed Critical Discourse Analysis involving an in-depth analysis of the grammar, narrative structure, word usage, and social context of the discourse representing gender injustice. The study is done to reveal how discourse can influence the formation of thought, culture, and power in society. The main data for this research is the film and its dialogue transcriptions. The analysis process focuses on in-depth analysis of conversations between characters and their interactions in order to reveal how female figures are depicted in the story. Sara Mills' discourse analysis theoretical framework is applied to dissect the choice of diction and sentence structure used to represent women, alongside the theory of subject position, object, and reader position. In line with the principles of CDA, which bridges textual analysis with broader socio-political critique, this study also incorporates feminist and gender theory to explore how these linguistic choices and positional roles perpetuate patriarchal power structures and ideologies within the societal context reflected in the film. The research results demonstrated gender biases and stereotypes in film dialogue, which reflected the condition of gender inequality in wider society. Analysis reveals that language actively reinforces existing power structures and gender disparities. These findings highlight the need for continued critical examination of gender representations in media. Future research should build on this work by applying evolving perspectives, such as intersectional feminism or queer theory, to analyze a wider array of cinematic works. This will foster an ongoing scholarly dialogue and provide deeper insights into the complex construction of gender in popular culture.